Educação para o empreendedorismo: práticas educacionais inovadoras no ensino superior - Marinho, Estêvão da Silva (2020)
The present study analyzes the implementation of a discipline, based on the interdisciplinary practices of education for entrepreneurship, and its influence on the self-efficacy and entrepreneurial intention of undergraduate students of a university, in the view of students and teachers. A mixed approach - qualitative and quantitative - of a descriptive, applied and exploratory nature was adopted, based on empirical research and, as a data collection strategy, the application of questionnaires, assessment, identification and observation instruments. In the qualitative approach, 11 documents that teach the discipline were chosen, and subsequently analyzed using content analysis techniques (BARDIN, 2014). In the quantitative approach, the self-efficacy scale in higher education (AEFS), developed by Polydoro and Guerreiro-Casanova (2010), and the entrepreneurial intention questionnaire (QIE), developed by Liñán and Chen (2009), were applied together with 122 undergraduate students at the Federal University of Santa Maria - RS. It is noteworthy that the application of questionnaires that occurred in two moments, at the beginning and at the end of the semester in a paired way, allowing a comparison between the two collections. As a result, it can be said that the participating students, evaluate in the indexes of self-efficacy and entrepreneurial intention after attending the discipline. Based on the triangulation of the data, one can infer this increase in the interdisciplinary practices of education for entrepreneurship adopted in the discipline entrepreneurial attitude in practice. Another result of this research was the finding of self-efficacy as a predictor of the studied students' entrepreneurial intention. As a suggestion for future studies, a comparison of results with other universities with similar disciplines is recommended, as well as comparisons with control groups.